A combined approach based on Subdivision Surface and Free Form Deformation for smart ship hull form design and variation. (3rd October 2018) - Coppedé, Antonio; Vernengo, Giuliano; Villa, Diego
ABSTRACT: Techniques for shape representation and further modification of a hull surface definitely play a key role in both the design of new buildings and in the optimisation of the existing ones. The simplification of the methods is the goal to reach in order to create useful tools for real applications. A new approach for hull shape modification is proposed. It is based on a combination of the Subdivision Surface technique for hull surface modelling and Free Form Deformation for shape variation. The formal relation between the two methods is established by the Free Form Deformation control volume and the Subdivision Surface control polygon, introducing significant simplification to the definition of the transformation. The new approach is described in detail highlighting its benefits. Its effectiveness is finally proved by an example of application on a real hull shape, where a combination of a local and global modification has been analysed.